Organization of the Addax Major Histocompatibility Complex Provides Insights Into Ruminant Evolution - Li, Chaokun; Huang, Rui; Nie, Fangyuan; Li, Jiujie; Zhu, Wen; Shi, Xiaoqian; Guo, Yu; Chen, Yan; Wang, Shiyu; Zhang, Limeng; Chen, Longxin; Li, Runting; et al. (Frontiers in Immunology, 2020)
Genetic signature of driving forces leading to the evolutionary success of ruminants remain largely unknown, although ruminants are critical in transferring solar energy fixed by plants into carnivorous species on our planet. In this study, we reported a complete map of major histocompatibility complex (MHC) of addax (Addax nasomaculatus) by sequencing a total of 47 overlapping BAC clones previously mapped to the MHC region. The Addax MHC is composed of 3,224,151 nucleotides, harboring a total of 150 coding genes, 50 tRNA genes and 14 non-coding RNA genes. We noticed that the organization of addax MHC is highly conserved to those of sheep and cattle, including a large piece of chromosome inversion that divided the MHC class II into IIa and IIb subregions. The percentage of interspersed elements in the addax MHC region was quite close to that of Caprinae. Phylogenetic analysis indicated that the ruminant-specific gene DY was close to DQ, and the estimated divergence time was about 140 million years ago. Homology modeling showed that the overall structure of DY in the addax was similar with that of HLA-DQ2. However, the pocket properties of P1, P4, P6 and P9, which were critical for antigen binding for the DY in the addax, showed distinctive features from those of HLA-DQ2. This suggested that populations of peptide antigens presented by DY in the addax and HLA-DQ2 were quite diverse, and the novel genes emerged at the boundaries between MHC class II and the chromosome inversion may have significantly enhanced the microbial regulation in the rumen of ruminant species, contributing to the enhanced ability in utilization of grass plants by ruminants. In summary, this study helped to enhance our understanding on MHC evolution, and the results supported our hypothesis that an ancient chromosome inversion in the MHC of the last common ancestor of ruminants may have contributed to the huge evolutionary success of ruminants.